2020
DOI: 10.3390/biom10111485
|View full text |Cite
|
Sign up to set email alerts
|

VDAC1 at the Intersection of Cell Metabolism, Apoptosis, and Diseases

Abstract: The voltage-dependent anion channel 1 (VDAC1) protein, is an important regulator of mitochondrial function, and serves as a mitochondrial gatekeeper, with responsibility for cellular fate. In addition to control over energy sources and metabolism, the protein also regulates epigenomic elements and apoptosis via mediating the release of apoptotic proteins from the mitochondria. Apoptotic and pathological conditions, as well as certain viruses, induce cell death by inducing VDAC1 overexpression leading to oligom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 352 publications
3
123
0
Order By: Relevance
“…It has been reported that the VDAC1 possesses Ca 2+ -binding sites, and its closure promotes Ca 2+ influx into mitochondria, which causes the opening of the mitochondrial permeability transition pore. Consequently, closure of the VDAC1 is recognised as a pro-apoptotic signal [ 25 ]. At the physiological state, [Ca 2+ ] in the mitochondrial intermembrane space is indistinguishable from that in the cytoplasm ([Ca 2+ ] c ) (around 100 nM) [ 26 ].…”
Section: Mitochondria-associated Membrane: a Platform For Er-mitochondria Ca 2+ Transportmentioning
confidence: 99%
“…It has been reported that the VDAC1 possesses Ca 2+ -binding sites, and its closure promotes Ca 2+ influx into mitochondria, which causes the opening of the mitochondrial permeability transition pore. Consequently, closure of the VDAC1 is recognised as a pro-apoptotic signal [ 25 ]. At the physiological state, [Ca 2+ ] in the mitochondrial intermembrane space is indistinguishable from that in the cytoplasm ([Ca 2+ ] c ) (around 100 nM) [ 26 ].…”
Section: Mitochondria-associated Membrane: a Platform For Er-mitochondria Ca 2+ Transportmentioning
confidence: 99%
“…Some phenolic compounds cause cell death by targeting mitochondria [ 4 , 10 , 17 ]. We took the advantage of the intrinsic fluorescence of curcumin ( Figure 2 a) to monitor its uptake and subsequent subcellular localization [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…VDAC is unique porin, functionally present and abundant in the outer mitochondrial membrane. It acts as the mitochondrial gatekeeper, mediating ionic and metabolic fluxes between the cytosol and the mitochondrial intermembrane space [ 15 , 16 , 17 ]. The selectivity of this exchange critically depends on the conformational state of VDAC.…”
Section: Introductionmentioning
confidence: 99%
“…Most current cancer chemotherapeutics cause cell death via apoptosis through two main apoptotic pathways: the extrinsic or death receptor pathway, and the intrinsic or mitochondrial pathway [ 1 , 2 ]. It is known that the mitochondrial apoptotic pathway is triggered by the opening of a large protein complex known as mPTP, although there is still much debate about mPTP components [ 5 , 39 , 40 , 41 , 42 ]. The human AACs [ 3 , 4 ] are among the most studied mPTP components/effectors and play a key role in regulating mPTP opening and thus in triggering the mitochondrial apoptotic pathway [ 5 , 6 , 7 , 39 , 40 , 41 , 43 ].…”
Section: Discussionmentioning
confidence: 99%